Abdominal Fibromyxoid Sarcoma in Pregnancy: An Unusual Cause of Preterm Labor and Sepsis - Abigail Barger; Maya Vishnia; Marie Hanna; Rebecca Horgan; Juliana Martins (Thieme Medical Publishers, Inc., 2024)
Cancer in pregnancy is rare, with incidence less than 1%, and the most common cancers being melanoma, breast, and cervical cancers. Fibromyxoid sarcoma is a soft tissue tumor involving deep soft tissues of the extremities and trunk, rarely located in the abdomen. A low-grade fibromyxoid sarcoma (LGFMS) falls in the family of fibrosarcoma. Only two cases of LGFMS in pregnancy have been reported. We report a case of abdominal LGFMS in pregnancy leading to preterm labor, sepsis, and an acute abdomen requiring surgery in the third trimester. A 19-year-old woman, gravida 1 at 32 weeks and 5 days presented to an outside hospital with preterm contractions and cervical effacement. She had a known abdominal mass, suspected to be accessory liver lobe, measuring 9.0 × 6.4 × 7.7 cm in the right upper quadrant. At 33 weeks of gestation, she developed fever and hypotension. Magnetic resonance imaging confirmed the presence of the mass, which was now on the left side of the abdomen and associated with a suspected abscess. She underwent cesarean delivery, and complete surgical resection of the mass along with a small bowel resection. Final pathology of the mass revealed a LGFMS. This case also highlights the need for a multidisciplinary approach to manage a rare presentation of sepsis and preterm labor in pregnancy.